Density functional approach to small fermion clusters - Kolehmainen, Jere (2000)
In this thesis we demonstrate the usefulness of the (current-)density-functional theory for studying different systems of identical fermions. Many properties of small fermion clusters are shown to be nearly independent of the interaction between the fermions. Small nuclei and clusters of alkali-metal atoms are shown to have similar shapes. Also their odd-even staggering of the total energy are shown to be of the same origin. An alternative model for linear nuclei is suggested. The interaction between small metal clusters and an inert surface is studied using a simple model. The clusters on the surface favour two-dimensional structures. Strictly two dimensional clusters and their deformations from non-rotationally symmetric state to rotationally symmetric state as a function of magnetic field is also studied. In addition to free clusters we have studied quantum dots where the electrons are bound by a rigid external potential. The coupling between magnetic dots can be either antiferromagnetic or ferromagnetic depending on the geometry. In a magnetic field the polarization of a quantum dot molecule starts at the contact region. Increasing the magnetic field the molecule first forms two maximum density droplets and eventually the electrons will localize.